Revitalisasi moral kewarganegaraan dalam ungkapan Jawa sebagai sumber pembentukan civic culture dan politic culture - Yoga Ardian Feriandi (Jurnal Civics: Media Kajian Kewarganegaraan, 2017)
This article aims to understand and multiply the moral values that exist in the expression of Java. Of the values excavated the hope can be a reference as the formation of civic culture and politic culture. The type of research used in this research is qualitative research, with descriptive-critical method, which in his explanation more emphasis on the power of data analysis on existing data sources. This study is based on library research. The object of the studies in the form of notes, transcripts, books, Journal of Research and so on which is linked to the study of Javanese culture, civic culture and politics culture. From the results of the discussion then known some phrases like aja dumeh, mendhem jero mikul dhuwur, jer basuki mawa bea. Having moral universal citizenship values so as to become a reference in order to form the civic culture which could further impact on politics culture as an effort to civil society in the Republic of Indonesia.